2015
DOI: 10.1111/jzo.12286
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour and energy budgets of sea snakes: insights from implanted data loggers

Abstract: Information on the foraging behaviour of sea snakes has the potential to clarify adaptive pathways involved in the evolutionary invasion of marine habitats by terrestrial vertebrates. However, logistical obstacles have precluded studies in this field. To obtain preliminary data of diving behaviour, we surgically implanted temperature‐depth loggers into two sympatric, amphibious, benthic foraging sea krait species from New Caledonia. Based on logger recovery from three snakes (1 Laticauda laticaudata and 2 L. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…move between the ocean and the land mostly from dusk to dawn (e.g. Shetty & Shine, 2002; Shine, et al., 2003; Shine, et al., 2003) but forage actively at sea at all hours of the day and night (Cook et al., 2016). Information on the other species is more fragmentary but Burns and Heatwole (1998) reported that radio‐tracked Aipysurus laevis foraged both by day and by night.…”
Section: Resultsmentioning
confidence: 99%
“…move between the ocean and the land mostly from dusk to dawn (e.g. Shetty & Shine, 2002; Shine, et al., 2003; Shine, et al., 2003) but forage actively at sea at all hours of the day and night (Cook et al., 2016). Information on the other species is more fragmentary but Burns and Heatwole (1998) reported that radio‐tracked Aipysurus laevis foraged both by day and by night.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Lutterschmidt et al (2006) implanted loggers into the general body cavity of free-ranging red-sided garter snakes (Thamnophis sirtalis parietalis) and recorded body temperatures during their winter dormancy. More recently, Cook et al (2016) used intraperitoneal implantation of a time-depth recorder and a radio-transmitter in sympatric sea kraits to investigate their at-sea foraging behavior and energy budgets.…”
Section: Methodsmentioning
confidence: 99%
“…Logistical impediments to observing snakes underwater are responsible for that lack of information. Recent developments in telemetry are providing far more detailed datasets on activity patterns and habitat use of marine snakes [15][16][17][18][19][20] but without direct information on behaviour. One striking exception involves studies showing that rising tides induce sea snakes (Hydrophis elegans and H. major) to shift habitat use (from open sites into seagrass beds) to avoid predation risk from sharks as water levels rise 21,22 .…”
mentioning
confidence: 99%